GAMBARAN PENGETAHUAN IBU NIFAS TENTANG PERAWATAN BAYI SEHARI HARI DI KELURAHAN TLOGOMAS WILAYAH KERJA PUSKESMAS DINOYO KOTA MALANG - Desy Dwi Cahyani; Vilanda Diah Ayu Safitri; Surachmindari .; Reni Wahyu Triningsih (Jurnal Pendidikan Kesehatan, 2020)
The lack of knowledge of post partum mothers in carrying out daily baby care can lead to undesirable conditions such as infection and even infant death. The purpose of this research is to find out the description of postpartum mothers knowledge about daily baby care. This research was conducted on May 17 until 23, 2019. The research design was quantitative descriptive with a total sampling of 21 respondents. The instrument used was a closed questionnaire used tryout method. Data processing using computer. The results showed the knowledge of postpartum mothers about daily baby care nearly half of the respondents were 10 people namely 47.62 percent with good knowledge. Good postpartum maternal knowledge about baby care will help reduce infant morbidity and mortality